Myopathies Associated with Statins Use in MI Patients (Medical Forum Monthly, 2024)
Objective: To determine the spectrum of myopathies in patients of MI after taking statins.Study Design: Observational / case-control study.Place and Duration of Study: This study was conducted at the Ayub Medical Complex, Abbottabad. It was conducted from Dec 2013 to May 2014.Materials and Methods: The study involved 100 known MI patients on statins of different ages and 100 control subjects. Their history regarding duration, dose, and muscle pain was taken and blood was collected for serum CPK. A relationship between duration of statin used and musle symptoms were studied.Results: chi-square test gives 10.4904 which is significant . The p-value is .0012. This result is significant at p < .05. There is a positive assosciation of CPK levels and muscle pain with odd ratio of 20.9. which shows a positive association .and 95% confidence interval shows a significant association with 9.7-41.4.p<0.000 which is highly significant.Conclusion: The study concluded that long term unchecked therapy of statin can cause severe damage to the body muscle even the heart muscles. So there should be proper follow up after 2-3 months to protect the patients from fatal myopathic effects.